Tracheal intubation while wearing personal protective equipment in simulation studies: a systematic review and meta-analysis with trial-sequential analysis - Filippo Sanfilippo; Stefano Tigano; Valeria La Rosa; Alberto Morgana; Paolo Murabito; Francesco Oliveri; Federico Longhini; Marinella Astuto (Brazilian Journal of Anesthesiology, 2022)
Background: Tracheal intubation in patients with coronavirus disease-19 is a high-risk procedure that should be performed with personal protective equipment (PPE). The influence of PPE on operator’s performance during tracheal intubation remains unclear. Methods: We conducted a systematic review and meta-analysis of simulation studies to evaluate the influence of wearing PPE as compared to standard uniform regarding time-to-intubation (TTI) and success rate. Subgroup analyses were conducted according to device used and operator’s experience. Results: The TTI was prolonged when wearing PPE (eight studies): Standard Mean Difference (SMD) -0.54, 95% Confidence Interval [-0.75, -0.34], p <  0.0001. Subgroup analyses according to device used showed similar findings (direct laryngoscopy, SMD -0.63 [-0.88, -0.38], p < 0.0001; videolaryngoscopy, SMD -0.39 [-0.75, -0.02], p =  0.04). Considering the operator’s experience, non-anesthesiologists had prolonged TTI (SMD -0.75 [-0.98, -0.52], p < 0.0001) while the analysis on anesthesiologists did not show significant differences (SMD -0.25 [-0.51, 0.01], p = 0.06). The success rate of tracheal intubation was not influenced by PPE: Risk Ratio (RR) 1.02 [1.00, 1.04]; p = 0.12). Subgroup analyses according to device demonstrated similar results (direct laryngoscopy, RR 1.03 [0.99, 1.07], p = 0.15, videolaryngoscopy, RR 1.01 [0.98, 1.04], p =  0.52). Wearing PPE had a trend towards negative influence on success rate in non-anesthesiologists (RR 1.05 [1.00, 1.10], p = 0.05), but not in anesthesiologists (RR 1.00 [0.98, 1.03], p = 0.84). Trial-sequential analyses for TTI and success rate indicated robustness of both results. Conclusions: Under simulated conditions, wearing PPE delays the TTI as compared to dressing standard uniform, with no influence on the success rate. However, certainty of evidence is very low. Performing tracheal intubation with direct laryngoscopy seems influenced to a greater extent as compared to videolaryngoscopy. Similarly, wearing PPE affects more the non-anesthesiologists subgroup as compared to anesthesiologists.